Management of Ankyloglossia in a Non-Syndromic Patient Using a Super Pulsed Laser: A Life-Changing Treatment- A Case Report - Jawed, Urfi; Zia, Afaf; Kumawat, Ramniwas; Bey, Afshan; Mahmood, Maahin (Journal of Dentistry Indonesia, 2023)
Objective: Ankyloglossia affects a person’s overall well-being and life, from malnutrition due to poor feeding and mechanical problems to psychological stress and low self-esteem, thus affecting social life. This case reports the use of non-scalpel techniques, such as a super pulsed laser, to manage ankyloglossia in a non-syndromic patient suffering from speech incompetence and restricted tongue mobility and highlights its advantages over other conventional techniques. Case Report: A 17-year-old male patient presented with a complaint of restricted tongue mobility, due to which he could not pronounce certain words clearly. As the patient was apprehensive about the use of a scalpel, it was decided to manage ankyloglossia using a diode laser against the conventional scalpel technique. Thus, the laser-assisted lingual frenectomy using GaAs super pulsed laser was used to excise the lingual frenulum. Conclusion: This case report suggests that ankyloglossia can be successfully treated by using laser-assisted surgery and gives superior results specifically in terms of lesser pain and bleeding.